Conceptualising guilt appeals in advertising : the mediating roles of inferences of manipulative intent and attitude towards advertising - Lwin, Michael (Curtin University, 2013)
This research developed and validated three guilt arousal scales specifically pertaining to existential, reactive and anticipatory guilt. It also provides a holistic model that investigates how ad credibility, attitude towards the advertisement, inferences of manipulative intent and purchase intention influence each type of guilt in three product categories in the luxury industry. It provides scholars, policy and decision makers a blueprint for strategic initiatives on the relative effectiveness of guilt appeals in the advertising industry.